Convergent validity and inter-rater reliability of a lower-limb multimodal physical function assessment in community-dwelling older adults - O’Brien, Myles W.; Neyedli, Heather F.; Bosquet, Laurent; Leadbetter, Brianna; Smith, Alex; Gallant, Francois; Tanguay, Pamela; Bélanger, Mathieu; Mekari, Said (Frontiers in Aging, 2023)
Introduction: Lower-limb physical function declines with age and contributes to a greater difficulty in performing activities of daily living. Existing assessments of lower-limb function assess one dimension of movement in isolation or are not time-efficient, which discourages their use in community and clinical settings. We aimed to address these limitations by assessing the inter-rater reliability and convergent validity of a new multimodal functional lower-limb assessment (FLA). Methods: FLA consists of five major functional movement tasks (rising from a chair, walking gait, stair ascending/descending, obstacle avoidance, and descending to a chair) performed consecutively. A total of 48 community-dwelling older adults (32 female participants; age: 71 ± 6 years) completed the FLA as well as timed up-and-go, 30-s sit-to-stand, and 6-min walk tests. Results: Slower FLA time was correlated with a slower timed up-and-go test (ρ = 0.70), less sit-to-stand repetitions (ρ = −0.65), and a shorter distance in the 6-min walk test (ρ = −0.69; all, p < 0.001). Assessments by two raters were not different (12.28 ± 3.86 s versus 12.29 ± 3.83 s, p = 0.98; inter-rater reliability ρ = 0.993, p < 0.001) and were statistically equivalent (via equivalence testing). Multiple regression and relative weights analyses demonstrated that FLA times were most predicted by the timed up-and-go performance [adjusted R2 = 0.75; p < 0.001; raw weight 0.42 (95% CI: 0.27, 0.53)]. Discussion: Our findings document the high inter-rater reliability and moderate-strong convergent validity of the FLA. These findings warrant further investigation into the predictive validity of the FLA for its use as an assessment of lower-limb physical function among community-dwelling older adults.